2013
DOI: 10.3389/fpsyt.2013.00115
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity as a “Translatable” Brain Marker Toward Early Intervention for Psychosis: A Review

Abstract: Recent reviews and meta-analyses suggest that reducing the duration of untreated psychosis leads to better symptomatic and functional outcome in patients with psychotic disorder. Early intervention attenuates the symptoms of individuals at clinical high-risk (HR) for psychosis and may delay or prevent their transition to psychosis. Identifying biological markers in the early stages of psychotic disorder is an important step toward elucidating the pathophysiology, improving prediction of the transition to psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 98 publications
5
97
1
Order By: Relevance
“…Greater discrepancies between deviant and standard memory traces (i.e., increasing deviance) are associated with larger MMN amplitudes and shorter latencies, both measures being correlated with behavioural discrimination of sounds (Näätänen et al 2012). Frequently found in SZ (vs. bipolar disorder), deficits in MMN generation are also observed in unaffected family members and first-episode patients (Sumiyoshi et al 2013;Nagai et al 2013aNagai et al , 2013bNäätänen et al 2014), and are exhibited in patients in response to a variety of auditory deviants, although duration deviant MMNs are viewed as being more trait specific for this disorder, while pitch and intensity deviant MMNs have shown different temporal changes over the course of the illness (Näätänen and Kahkonen 2008;Todd et al 2008). Impaired MMN generation in SZ is linked to structural (Rasser et al 2011;Salisbury et al 2007) and functional (Javitt 2000;Light and Braff 2005) impairments in the auditory sensory cortex and correlates with negative symptoms and poor executive functioning (Kiang et al 2007;Näätänen et al 2004;Turetsky et al 2009;Umbricht et al 2006) as well as deficits in social/occupational functioning (Lee et al 2014;Light and Braff 2005), while in healthy volunteers, the greater the MMN amplitude, the stronger the functional status of the individual .…”
Section: Introductionmentioning
confidence: 98%
“…Greater discrepancies between deviant and standard memory traces (i.e., increasing deviance) are associated with larger MMN amplitudes and shorter latencies, both measures being correlated with behavioural discrimination of sounds (Näätänen et al 2012). Frequently found in SZ (vs. bipolar disorder), deficits in MMN generation are also observed in unaffected family members and first-episode patients (Sumiyoshi et al 2013;Nagai et al 2013aNagai et al , 2013bNäätänen et al 2014), and are exhibited in patients in response to a variety of auditory deviants, although duration deviant MMNs are viewed as being more trait specific for this disorder, while pitch and intensity deviant MMNs have shown different temporal changes over the course of the illness (Näätänen and Kahkonen 2008;Todd et al 2008). Impaired MMN generation in SZ is linked to structural (Rasser et al 2011;Salisbury et al 2007) and functional (Javitt 2000;Light and Braff 2005) impairments in the auditory sensory cortex and correlates with negative symptoms and poor executive functioning (Kiang et al 2007;Näätänen et al 2004;Turetsky et al 2009;Umbricht et al 2006) as well as deficits in social/occupational functioning (Lee et al 2014;Light and Braff 2005), while in healthy volunteers, the greater the MMN amplitude, the stronger the functional status of the individual .…”
Section: Introductionmentioning
confidence: 98%
“…A later study (Kiang et al 2009) of large groups of participants found a significant reduction in duration MMN amplitude with age in both healthy controls and schizophrenia patients aged between 18 and 65 years old. A study which compared frequency and duration deviance MMN found that duration MMN was more stable over the course of schizophrenia (Michie et al 2000); there is however evidence that the reduction in duration MMN is greater in the early stages of schizophrenia or even in patients in the prodromal stage (Bodatsch et al 2011;Perez et al 2014;Higuchi et al 2014;Hermens et al 2010;Jahshan et al 2012;Nagai et al 2013a); similar findings have been reported for the magnetic counterpart of MMN (Shin et al 2012).…”
Section: "State Of the Art" -Mmn In Schizophreniamentioning
confidence: 54%
“…This refers to bridging the gap between human and primate brain imaging by using a measurement method commonly used in both species (e.g., MRI, ECoG, EEG, etc.) (Nagai et al, 2013). The concept of the realworld measurement should be incorporated and integrated into the endeavor of establishing translatable brain markers in neurocircuit research.…”
Section: Integration With Comparative Neurosciencementioning
confidence: 99%